ABOUT WITH PECULIARITIES OF EATING BEHAVIOR AND QUALITY OF LIFE IN ELDERLY AND SENILE PEOPLE WITH OBESITY AND COMORBIDITY - Negmatova, Gulzoda Shukhratovna; Mansurova , Gulsum Zaydinovna; Abdiyev , Lazizbek Sobir oʻgʻli (Educational Research in Universal Sciences, 2024)
The new trend is characterized by the rapid spread of obesity and associated diseases. Considering the fact that the life expectancy of the planet's population is increasing, the problem of the spread of obesity and associated diseases, leading to a deterioration in the quality of life in elderly and senile patients, will become extremely relevant. There is evidence that overweight and obesity are protective in acute myocardial infarction (AMI), resulting in less myocardial damage. The obesity paradox in patients with AMI is a real phenomenon confirmed in a large prospective study by the CCP (the Cooperative Cardiovascular Project) of the medical records of elderly Medicare patients hospitalized with AMI, with a 17-year follow-up (n=124,981) to evaluate the association. higher BMI with short- and long-term survival after AMI (Cox proportional hazards models were used). Life expectancy estimates tended to be lowest for morbidly obese patients and highest for overweight patients [6].